Atomistic Simulations of Compression Tests on Ni3Al Nanocubes - Amodeo, Jonathan; Begau, C.; Bitzek, Erik (Materials Research Letters, 2014)
The deformation behaviour of nano-sized Ni3Al cubes with 100 side surfaces is investigated under uniaxial compression using constant-temperature molecular dynamics simulations at 300 K. The simulations reproduce key features of recently performed nanocompression experiments, namely the lack of strain hardening, homogeneous deformation of the entire sample and overall high stress levels of the order of 3-5 GPa. According to the simulations, the critical initial step is the formation of a pseudo-twin structure, which then further deforms by Shockley partial dislocations. These deformation mechanisms differ significantly from bulk Ni3Al and are rationalized in terms of generalized stacking fault energies and resolved shear stresses.
Keywords: Small-Scale Plasticity; MD Simulations; Ni3Al; Dislocations; Twinning